ANALISIS PENGARUH ABUSIVE SUPERVISION TERHADAP INTENTION TO QUIT DENGAN BURNOUT SEBAGAI VARIABEL MEDIASI (Studi pada karyawan PT Karya Mina Putra Rembang) - Purnomo, Igas Aji; Lataruva, Eisha (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to examine the effect of abusive supervision on intention to quit mediated by burnout on employees of PT Karya Mina Putra in Rembang. Abusive supervision was measured by Tepper indicators (2000). The intention to quit variable uses a measurement scale from Sjöberg and Sverke (2000). Burnout which as a mediating variable was measured by the Maslach Burnout Inventory indicator (1996). The sample used in this study was employees of PT Karya Mina Putra in 2023. The number of samples were 84 employees.Sampling in this study using a accidental sampling technique with a questionnaire in the method of collecting data on respondents. While the analysis used is Partial Least Square (PLS) analysis with the help of SmartPLS version 3 software The results showed that abusive supervision had no effect on intention to quit. Abusive supervision had an effect on burnout. Burnout had an effect on affects the intention to quit. In addition, burnout also partially mediates the relationship between abusive supervision and intention to quit and the burnout is able to become an intervening variable between abusive supervisors and the intention to quit.